Pre-conception Nutrition Care, Nutritional Knowledge, Nutritional Practices, and cultural Belief among pregnant women: A Qualitative Study in Aceh - Aripin Ahmad; Silvia Wagustina; Wiwit Estuti; Syuja’ Rafiqi Arifin (Journal of Nutrition Science, 2020)
Health care during pre-conception and pregnancy is one of the important factors that can improve pregnancy outcomes. This study aims to explore how pre-conception care, nutrition knowledge and practices, and the factors that influence it in pregnant women. This study used a cross-sectional design with a qualitative study approach. The subject was 11 pregnant women who were selected as well as 5 health workers. The data pre-conception of care and nutrition practices before pregnant, nutrition knowledge and nutrition practices, food taboo and suggestion, cultural belief influence, and data sources of information and nutritional information needs was carried out using the Focus Group Discussion. The results showed that most of the pregnant women did not get and done pre-conception nutrition care, had insufficient nutritional knowledge and the practice of balanced nutrition was still low. There is still an influence of cultural belief in the form of food taboos and food suggestions, and the lack of sources of information and nutritional information towards nutrition practice. It is necessary to develop media and nutrition educational methods to improve nutrition and health care  during pre-conception and pregnancy, and further studies are needed specifically on the role of family factors, especially grandmothers, mothers in-laws, and family members on nutrition practices in pregnant women.